The Concept of Coworking : Methodological Considerations and Coworking Dynamics - Mayerhoffer, Manuel; Lukeš, Martin, 1976-; Dvouletý, Ondřej; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2022)
Changes in the nature of work and the rise of the knowledge economy have prompted a significant shift in both how and where knowledge work is being done. As part of this, coworking spaces have gained strong traction as collaborative workspaces for unaffiliated professionals. In the wake of the COVID-19 pandemic, the complex functioning and rapid development of the concept of coworking, with its growing importance for the post-COVID-19 workplace, warrant further investigation in support of this thriving and still young field of research. That said, this doctoral thesis comprises a total of five journal articles and a paper under review, which contribute to the concept underpinning the coworking phenomenon, its rise and dynamics, as well as suitable methodological approaches for its exploration. Following the discussion of the main objectives of the thesis, an extensive commentary is provided on the various themes and papers. The first paper is concerned with the methodological underpinnings of the open-plan office paradox and provides a systematic literature review on the state of the field. Focusing on coworking as a distinct case of open-plan office, the thesis goes on to explore contemporary qualitative research methods for the exploration of these coworking environments. Subsequently, the rise of the coworking industry is discussed with the example of Prague as a rising hub. These first three methodological and conceptual papers are bolstered with empirical evidence. The fourth paper explores coworking spaces as talent hubs, drawing on qualitative data obtained from twenty coworking spaces in the Visegrad region. Like the rest of the business world, coworking spaces have been heavily disrupted by the COVID-19 pandemic.
For this reason, an empirical study is presented, which investigates the economic impact of the pandemic, strategies employed, and expectations for the future based on quantitative data obtained from coworking space operators and employees in Germany as one of the fastest-growing markets prior to the pandemic. Lastly, the thesis delves into the aftermath of the COVID-19 pandemic within coworking spaces, exploring the impact on the shift in communality and coworking space user outcomes based on rich qualitative data. Overall, the thesis contributes to the understanding and research leading into the post-COVID-19 coworking phenomenon.
Vedoucí práce: Martin Lukeš
Disertační práce (Ph.D.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2022
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2022
Způsob přístupu: Internet
Keywords: podniková ekonomika a management [obor disert. práce]; disertace; dissertations